QOS measurement and evaluation procedure in a telecommunications network (Inflexion Point Magazine, 2026)
In most telecommunications networks where VoIP has been implemented, the quality levels offered are not adequately assessed, which is essential for their improvement and commercialization. This article develops a procedure for measuring and evaluating QoS in VoIP, applicable to both fixed and mobile networks. Key parameters, such as delay, jitter, and packet loss, are identified, and measurement methods tailored to each network type are established. The procedure is validated through its application in real-life scenarios in one telecommunications network, demonstrating its effectiveness in providing an accurate QoS assessment and allowing the provider to continuously improve the quality of service in both environments.
Keywords: Quality of Service (QoS); Voice Over IP (VoIP); Mobile Network; Nauta-Hogar; Public Wi-Fi; Measurement; Evaluation; Parameters